2020
DOI: 10.1183/13993003.01811-2020
|View full text |Cite
|
Sign up to set email alerts
|

Elevated D-dimers and lack of anticoagulation predict PE in severe COVID-19 patients

Abstract: BackgroundCOVID-19 may predispose to venous thromboembolism. We determined factors independently associated with computed tomography pulmonary angiography (CTPA)-confirmed pulmonary embolism (PE) in hospitalised severe COVID-19 patients.MethodsAmong all (N=349) patients hospitalised for COVID-19 in a university hospital in a French region with a high rate of COVID-19, we analysed patients who underwent CTPA for clinical signs of severe disease (SpO2≤93% or breathing rate≥30/min); or rapid clinical worsening. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
128
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(159 citation statements)
references
References 39 publications
12
128
4
2
Order By: Relevance
“…9 ± 8.2 vs 68.6 ± 19.3 22 (81.5) vs 224 (55.7) NA NA 6 (22.2) vs 99 (24.6) 8 (29.6) vs 96 (23.9) 2 (7.4) vs 36 (9.0) NA 2 (7.4) vs 57 (14.2) 22.5 ± 9.3 vs 8.6 ± 6 18 (66.7) vs 76 (18.9) 18 (66.7) vs 55 (13.7) Bompard F(26) France retrospective cohort 135 PE; 32 ( 24 ) 68.6 ± 14 vs 63.35 ± 17.3 26 ( 81 ) va 68 ( 66 ) NA NA NA NA NA NA 4 ( 13 ) vs 12 ( 12 ) 7 ± 6.2 vs 5.7 ± 3 12 ( 38 ) vs 12 ( 12 ) 10 ( 31 ) vs 8 ( 8 ) Avruscio G(27) Italy observational cohort 85 VTE; 43 ( 51 ) NA NA NA NA NA NA NA NA 8 ( 19 ) vs 0 (0) NA NA NA Gibson C J(28) ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 ± 8.2 vs 68.6 ± 19.3 22 (81.5) vs 224 (55.7) NA NA 6 (22.2) vs 99 (24.6) 8 (29.6) vs 96 (23.9) 2 (7.4) vs 36 (9.0) NA 2 (7.4) vs 57 (14.2) 22.5 ± 9.3 vs 8.6 ± 6 18 (66.7) vs 76 (18.9) 18 (66.7) vs 55 (13.7) Bompard F(26) France retrospective cohort 135 PE; 32 ( 24 ) 68.6 ± 14 vs 63.35 ± 17.3 26 ( 81 ) va 68 ( 66 ) NA NA NA NA NA NA 4 ( 13 ) vs 12 ( 12 ) 7 ± 6.2 vs 5.7 ± 3 12 ( 38 ) vs 12 ( 12 ) 10 ( 31 ) vs 8 ( 8 ) Avruscio G(27) Italy observational cohort 85 VTE; 43 ( 51 ) NA NA NA NA NA NA NA NA 8 ( 19 ) vs 0 (0) NA NA NA Gibson C J(28) ...…”
Section: Resultsmentioning
confidence: 99%
“… UK Retrospective study 84 PE; 32 (38.1) 60.97 ± 11.64 vs 59.00 ± 19.07 17 ( 53 ) vs 25 ( 48 ) NA NA NA NA NA NA NA NA NA NA Maatman T K(39) US Observational 109 VTE; 31 (28.4) 60 ± 17 vs 62 ± 15 20 ( 65 ) vs 42 ( 54 ) 34.7 ± 12.7 vs 34.8 ± 11.5 17 ( 55 ) vs 57 ( 73 ) 10 ( 32 ) vs 33 ( 42 ) NA 3 ( 10 ) vs 14 ( 18 ) 5(16) vs 28 ( 36 ) 8 (25.8) vs 19 (24.4) NA NA NA Artifoni M(40) France Retrospective cohort 71 VTE; 16 (22.5) 60.2 ± 31.05 vs 62.06 ±20.94 11 (68.7) vs 32 (58.2) 27.22±2.93 vs 28±6.17 3 ( 19 ) vs 26 ( 47 ) 0 (0) vs 14 ( 25 ) NA …”
Section: Resultsmentioning
confidence: 99%
“…Patients with high D-dimer levels have an increased risk of VTE [54], and high D-dimer levels are associated with an increased risk of mortality in SARS-CoV-2 patients [55,56]. However, the value of this laboratory parameter for predicting VTE in COVID-19 is debatable, as the study results disagree regarding the degree of association between D-dimer levels and VTE occurrence [29,57] and in terms of D-dimer being an independent predictor of VTE in COVID-19 patients [58,59]. The literature also suggests that, compared with D-dimer, the prothrombin fragment Only one study that we included showed higher values of CT and A10 in patients with markedly elevated D-dimer levels [35].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Simple and minimally-invasive diagnostic algorithms that can safely rule-out PE in patients with COVID-19 are urgently needed. Therefore, we read with interest the recent paper by Mouhat and colleagues in the European Respiratory Journal [ 2 ].…”
mentioning
confidence: 99%
“…Whether similar D-dimer thresholds can be applied in COVID-19 patients suspected of PE is unknown, because COVID-19 triggers a hyperinflammatory state with endothelial activation and high D-dimer levels [ 7 ]. In their article, Mouhat and colleagues propose a threshold of 2590 ng·mL −1 [ 2 ]. This threshold was not selected to obtain an NPV close to 100%, but it was based on the highest “Youden's index”.…”
mentioning
confidence: 99%